The ins and outs of host‐microsporidia interactions during invasion, proliferation and exit - Tamim El Jarkass, Hala; Reinke, Aaron W. (Cellular microbiology, 2020)
Microsporidia are a large group of fungal‐related obligate intracellular parasites. They are responsible for infections in humans as well as in agriculturally and environmentally important animals. Although microsporidia are abundant in nature, many of the molecular mechanisms employed during infection have remained enigmatic. In this review, we highlight recent work showing how microsporidia invade, proliferate and exit from host cells. During invasion, microsporidia use spore wall and polar tube proteins to interact with host receptors and adhere to the host cell surface. In turn, the host has multiple defence mechanisms to prevent and eliminate these infections. Microsporidia encode numerous transporters and steal host nutrients to facilitate proliferation within host cells. They also encode many secreted proteins which may modulate host metabolism and inhibit host cell defence mechanisms. Spores exit the host in a non‐lytic manner that is dependent on host actin and endocytic recycling proteins. Together, this work provides a fuller picture of the mechanisms that these fascinating organisms use to infect their hosts.